Alpinia conchigera antifungal activity against oral Candida: an in vitro study - Nur Umairah Atiqah Sabri; Nor Syazwani Muhammad Zahidan; Siti Noor Adnalizawati Adnan; Zulfahmi Said; Khalijah Awang; Haslinda Mohd Salleh; Normaliza Ab Malik (Penerbit Universiti Kebangsaan Malaysia, 2025)
Candida species are the dominant inhabitants in the oral cavity and can potentially develop into opportunistic pathogens in immunocompromised individuals, leading to oral infections. The emergence of Candida resistance against antifungal drugs has called for an alternative. This study aimed to evaluate the antifungal efficacy of n-hexane extract and its bioactive compound, 1’-S-1’-acetoxychavicol acetate (ACA), isolated from the rhizome of Alpinia conchigera against oral Candida. A crude n-hexane extract (HE) was obtained from the dried, ground A. conchigera rhizome using the maceration technique. The HE was subjected to column chromatography to isolate ACA, followed by structural elucidation and purity confirmation using nuclear magnetic resonance (NMR) and high-performance liquid chromatography (HPLC). Oral Candida species were retrieved from the oral rinses of the older adults. The antifungal effects of HE and ACA against oral Candida isolates were screened using the disc diffusion assay, followed by an evaluation of minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC). A total of 21.391 g of HE was obtained, yielding 3.7573 mg of ACA with a purity of 93.67%. The largest inhibition zones were observed for HE and ACA, both at a concentration of 100 mg/mL against C. albicans (12.0 ± 0.8 mm) and C. glabrata (10.0 ± 0.8 mm), respectively. The MIC and MFC values of HE ranged from 0.7 to 12.5 mg/mL and from 0.7 to 25 mg/mL, respectively. Meanwhile, for ACA, both MIC and MFC values are within the range of 0.7 to 25 mg/mL. This in vitro study showed that both HE and ACA possess antifungal properties against Candida isolates, which highlights their potential as natural antifungal agents for incorporation into oral care products.